2018
DOI: 10.1101/424721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-Wide Associations with Resistance to Bipolaris Leaf Spot (Bipolaris oryzae (Breda de Haan) Shoemaker) in a Northern Switchgrass Population (Panicum virgatum L.)

Abstract: Switchgrass (Panicum virgatum L.), a northern native perennial grass, suffers from yield reduction from Bipolaris leaf spot caused by Bipolaris oryzae (Breda de Haan) Shoe-maker. This study aimed for determining the resistant populations via multiple phenotyping approaches and identifying potential resistance genes to the disease from genome-wide association studies in the switchgrass northern association panel. The disease resistance was evaluated from both natural (field evaluations in NY and PA) and artific… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Gustafson et al (2003) indicated that both additive and nonadditive genetic variation could be exploited for improving rust resistance by selecting among and within families in switchgrass breeding populations. Leaf spot disease, caused by Bipolaris spp., affects switchgrass in the eastern and southern regions of the United States (Fajolu, 2012;Songsomboon et al, 2019). For all other diseases of switchgrass, however, the potential for improvement of resistance has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Gustafson et al (2003) indicated that both additive and nonadditive genetic variation could be exploited for improving rust resistance by selecting among and within families in switchgrass breeding populations. Leaf spot disease, caused by Bipolaris spp., affects switchgrass in the eastern and southern regions of the United States (Fajolu, 2012;Songsomboon et al, 2019). For all other diseases of switchgrass, however, the potential for improvement of resistance has not been explored.…”
Section: Introductionmentioning
confidence: 99%